2020
DOI: 10.1128/aac.02231-19
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Activity of a Combination of Three Bacteriophages Alone or in Association with Antibiotics on Staphylococcus aureus Embedded in Biofilm or Internalized in Osteoblasts

Abstract: Staphylococcus aureus is responsible for difficult-to-treat bone and joint infections (BJIs). This is related to its ability to form biofilm and to be internalized and persist inside osteoblasts. Recently, bacteriophage therapy has emerged as a promising option to improve treatment of such infections, but data on its activity against the specific bacterial lifestyles presented above remain scarce. We evaluated the activity of a combination of three bacteriophages, recently used for compassionate treatment in F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 33 publications
(39 reference statements)
2
39
0
1
Order By: Relevance
“…In all the reviewed studies, bacteriophage was active against both planktonic cells and biofilm, showing a bactericidal effect and detachment activities against tested pathogens. Out of the nine studies, two evaluated the effect of combination therapy of phage with antibiotics against S. aureus using vancomycin/rifampicin, and teicoplanin, respectively [ 35 , 43 ]. The first S. aureus study illustrated a synergistic effect between vancomycin/rifampicin, and bacteriophage when phage was administered directly to tissue culture plates at a low concentration of phage (10 5 PFU/mL) and vancomycin (6 mg/L)/rifampicin (MIC of 0.016 mg/L) [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…In all the reviewed studies, bacteriophage was active against both planktonic cells and biofilm, showing a bactericidal effect and detachment activities against tested pathogens. Out of the nine studies, two evaluated the effect of combination therapy of phage with antibiotics against S. aureus using vancomycin/rifampicin, and teicoplanin, respectively [ 35 , 43 ]. The first S. aureus study illustrated a synergistic effect between vancomycin/rifampicin, and bacteriophage when phage was administered directly to tissue culture plates at a low concentration of phage (10 5 PFU/mL) and vancomycin (6 mg/L)/rifampicin (MIC of 0.016 mg/L) [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…The activity of these two bacteriophages against the biofilm-embedded S. aureus was dose dependent. In addition, synergistic effects were observed when the bacteriophages were combined with antibiotics used at the lowest concentrations (5).…”
Section: Discussionmentioning
confidence: 99%
“…Lytic bacteriophages rapidly kill in vitro specifically the targeted bacteria and self-replicate in an exponential and self-sustained reaction ( 4 ). They are considered to have a high potential in patients with PJI as it has been demonstrated that they have a synergistic anti-biofilm activity with antibiotics ( 5 ). In a few patients with relapsing chronic PJI for whom explantation was not possible, we previously performed DAIR and used a selected cocktail of bacteriophages that was injected into the joint as compassionate therapy, with a good clinical response ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that the time and order of treatment are important to improve antibiofilm properties of combination with antibiotics [ 107 , 108 ]. As host cells can potentially represent a reservoir of internalized bacteria and a source of reinfection, targeting internalized bacteria in cells would be a huge advantage, but there is a lack of efficiency of bacteriophages against internalized bacteria such as S. aureus [ 109 ].…”
Section: Emergent Antibiofilm Strategies In Periprosthetic Joint Imentioning
confidence: 99%